Manajemen Pendidikan Literasi Finansial Anak Usia Dini - Revita Yanuarsari; Lisnawati; Ella Dewi Latifah (Jurnal Pendidikan dan Kebudayaan (JURDIKBUD), 2023)
Management of financial literacy education is an important aspect in children's development from an early age. The ability to manage money and understand financial concepts are crucial skills for everyday life. Therefore, management of financial literacy education for early childhood is a relevant topic and needs serious attention. This research aims to investigate effective management methods and strategies in providing financial literacy education to young children. Through a qualitative approach, this research analyzes various resources that can be used in the context of financial literacy education for early childhood. These resources include storybooks, educational games, practical activities, as well as the role of teachers and parents in the educational process.